NIMG-19. SEX-SPECIFIC BRAIN MAPS FOR RISK OF SEIZURE AMONG GLIOMA PATIENTS. (5th November 2018) - Ranjbar, Sara; Anderies, Barrett; Singleton, Kyle; Johnston, Sandra; Rickertsen, Cassandra; Sharma, Akanksha; Porter, Alyx; Mrugala, Maciej; Hu, Leland; Mitchell, Joseph; Rubin, Joshua; Swanson, Kristin
Abstract: PURPOSE: Despite a growing body of research on the etiology of seizures in the brain tumor population, it is not yet clear why approximately one third of this population presents with seizure. In this retrospective study we seek to assess the impact of tumor location on the risk of seizure among male and female glioma patients, respectively. METHODS: From our multi-institutional database, we selected adult patients with contrast-enhancing gliomas (any grade) and known seizure-presentation status at initial diagnosis. Tumors were segmented on pretreatment T2-FLAIR, T2, and post-gadolinium T1 (T1Gd) MR sequences. We warped cortical and subcortical probabilistic atlases to patient images and estimated tumor burden (%) on structures within each lobe and the deep brain. We calculated risk of seizure for various levels of tumor burden and used the result to create sex-specific risk-maps<./p> RESULTS: Our cohort included 128 patients (47 females, 81 males) among whom tumors presented with seizure in 34% of females (n=18) and 58% of males (n=47). Patients with tumors in deep brain structures were identified as at risk for seizure in both males and females. In female patients T2 hyperintensity on 44% of right frontal lobe or 28% of left parietal lobe seem to have an estimated 50%+ risk of seizure. Data indicate that in male patients with left-sided tumors, T2 hyperintensity on 30% or more of frontal, temporal, or parietal lobes results in 50%+ risk of seizure. Male patients with right side tumors, showed a similar level of risk for T2 presence in lateral ventricles and parietal lobe. CONCLUSION: This study reveals that the risk of seizure is specific to the location of glioma, the percentage of tumor burden, and patient sex. These differences could be considered in patient management decisions to more selectively prescribe anticonvulsants and optimize patient care.